EKSISTENSI HUKUM PIDANA ADAT NGATA TORO KECAMATAN KULAWI DAN KEDUDUKANNYA DALAM HUKUM PIDANA NASIONAL - Rahmat Hidayat (Maleo Law Journal, 2017)
Indonesia is a constitutional state, it is contained in Article 1 Paragraph (3) of the Constitution of the Republic of Indonesia 1945. The law is divided into two namely Written and Unwritten Law Before the formation of positive law in the community, customary law becomes a law governing the life of the community, Adat Ngata Toro. Customary law in Ngata Toro itself is formed from the customs that exist in public life, so that customary law in Ngata Toro develop dynamically in accordance with the times. The form is not codified cause customary law is not a source of law that has the principle of legality, but the values of customary law becomes a source of important role in the formation of a positive law in a country. This research uses Normative Empirical Research Method. Because Customary Law in Toro village is an unwritten and un codified rule, but still applied, obeyed and respected. In fact, within a lawful state, the principle of legality applies.Keywords : Existence, Customary Criminal Law, Village Toro